Crystal structure, thermal and magnetic behavior of inorganic-organic hybrid [VIV 4O10 VV 2O4] (C6H14N2) •H2O polymeric framework - Thapanon Settheeworrarit (2018)
The inorganic-organic hybrid [VIV4O10VV2O4] (C6H14N2)•H2O polymeric framework was prepared under mild hydrothermal conditions from a mixture of DABCO and V2O5in deionized water with a 1:1:450 mole ratio, at neutral pH. The reaction was carried out at 180°C for 3 days under autogenous pressure yielding phase pure crystals product. The crystal structure was studied using both powder and single crystal X-ray crystallography, revealing the structure to be of the (UuDd:T*)α′ type in the SP+T class and Z-T subclass. The presence of the organic cation was confirmed by FT-IR spectrum and chemical composition analysis. The structure was thermally stable up to over 400°C, and showed ferromagnetic character at room temperature with the maximum molar susceptibility of 8.26 × 10-3emu/mol-1at zero applied field. © 2006 Springer Science+Business Media, LLC.